2006
DOI: 10.1111/j.1460-9592.2006.02128.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood obesity and anesthetic morbidity

Abstract: Our study demonstrated a small increase in minor respiratory complications in obese children who underwent anesthesia. Inhalation induction was not associated with an increase in adverse events in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
41
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 20 publications
1
41
0
2
Order By: Relevance
“…The treatment of nonunions in obese patients has been shown to be fraught with complications [6]. Anesthesia risks also increase for obese children [11,12]. Previous study of femur fractures treated with intramedullary elastic nails in children has suggested that larger children have a higher complication rate [2].…”
Section: Discussionmentioning
confidence: 99%
“…The treatment of nonunions in obese patients has been shown to be fraught with complications [6]. Anesthesia risks also increase for obese children [11,12]. Previous study of femur fractures treated with intramedullary elastic nails in children has suggested that larger children have a higher complication rate [2].…”
Section: Discussionmentioning
confidence: 99%
“…18 A retrospective chart review of 1,133 children who underwent outpatient dental procedures revealed an increased incidence of oxygen desaturation requiring supplemental oxygen and unplanned overnight stay in obese children postoperatively. 19 These studies demonstrate the increased risk of respiratory compromise that may be seen in the postsurgical obese pediatric patient, and suggest that overnight stays are indicated to assure postoperative surveillance of the potential of these adverse events.…”
Section: Postoperative Considerationsmentioning
confidence: 96%
“…A retrospective study of 1,133 children undergoing planned outpatient dental procedures under anaesthesia at an American children's hospital showed that obese children were more likely to suffer respiratory complications than non-obese children, leading to arterial oxygen desaturation and unexpected hospitalisation (2 vs. 0.19 % in both situations). These findings suggest that identification and awareness of childhood obesity as a risk factor for perioperative complications is important for optimising anaesthetic management and outcomes [26].…”
Section: Cardiac Arrest and Mortality In Paediatric Anaesthesiamentioning
confidence: 97%